К распространению в Мировом океане нематод, обнаруженных у рыб южных морей - Парухин, А.М. (Вестник зоологии, 1975)
In different regions of the World Ocean 65 Nematoda species were found in 6500 fish belonging to 200 species of 100 families. The Nematoda fauna is established to be poorer in the Southern Atlantic and considerably richer in the Indian and Pacific Oceans. The species composition of the Nematoda fauna in fish of the northern hemisphere is richer than that of the southern hemisphere. The Nematoda larvae of the family Anisakidae Skrjabin et Karokhin, 1945 are widely distributed in the World Ocean. Nematoda of the family Capillariidae Neweu-Lemaire, 1936 were not found in the South Atlantic and Nematoda of the family Dracunculidae Leiper, 1912 were met there only once, while in the Indian and Pacific Oceans representatives of the both families are widely distributed. Zoogeographic analysis of the found Nematoda is given.